Blunted reward responsiveness prospectively predicts emotional distress when exposed to a naturalistic stressor. (26th December 2022) - Yan, Linlin; Kohn, Nils; Yi, Wei; Wang, Naiyi; Duan, Hongxia; Wu, Jianhui
Abstract: Both stress and blunted reward responsiveness have been identified as core risk factors of depression. Whether blunted reward responsiveness increases psychological vulnerability to real‐life stress from a dynamic perspective (from stress reactivity to recovery) has not been investigated. By utilizing a real‐world stressful event (i.e. the final examination), this study aimed to explore the role of reward responsiveness in the stress‐emotional distress relationship during stress reactivity and recovery phases. We followed 57 undergraduates with three assessments, from six weeks before examination weeks (T1, baseline), one day before the examinations (T2) to two weeks after the examinations (T3), therefore, covering stress reactivity (T1 to T2) and recovery (T2 to T3) phases. At baseline, reward responsiveness was measured as the Reward Positivity (RewP) in the doors task. Stress and emotional distress (anxiety and depression) were reported at T1, T2 and T3 to capture their dynamic changes. Results showed that self‐report stress levels significantly increased from T1 to T2 (stress reactivity phase) and decreased from T2 to T3 (stress recovery phase). Furthermore, blunted reward responsiveness at baseline prospectively predicted emotional distress during the stress reactivity phase but not the recovery phase. Specifically, during the stress reactivity phase, higher perceived stress was associated with greater anxiety and depression only in participants with relatively smaller residual RewP amplitudes but not in participants with relatively larger residual RewP amplitudes. Our study demonstrated that a blunted reward responsiveness is a vulnerable factor of depression, especially when exposed to stress. Our findings provide insights into prevention and intervention for stress‐related disturbance.